Prognostic significance of copy number variation in B-cell acute lymphoblastic leukemia - Song, Yang; Fang, Qiuyun; Mi, Yingchang (Frontiers in Oncology, 2022)
Copy number variations (CNVs) are widespread in both pediatric and adult cases of B-cell acute lymphoblastic leukemia (B-ALL); however, their clinical significance remains unclear. This review primarily discusses the most prevalent CNVs in B-ALL to elucidate their clinical value and further personalized management of this population. The discovery of the molecular mechanism of gene deletion and the development of targeted drugs will further enhance the clinical prognosis of B-ALL.